Óleos essenciais e seus constituintes para o controle de Cryptotermes brevis e Nasutitermes corniger : vias de exposição e respostas comportamentais - Santos, Abraão Almeida (2016)
Termites display a key role in the terrestrial ecological ecosystems by positively contributing to maintenance of these ecosystems. However, despite this importance, some species are known as urban, forests, and agriculture pests. At urban areas, Cryptotermes brevis (Kalotermitidae) and Nasutitermes corniger (Termitidae: Nasutitermitinae) species are because of its attack to structure and wood pieces, causing a high damage to those materials. The use of conventional insecticide is the main control method for these pests. However, the adverse effects in the use of these products, and the demand for others with lower toxicological risks have been motivating the realization of research with natural products. Thus, in this study, we evaluate the lethal, and sub lethal effects of Aristolochia trilobata (Aristolochiaceae) and Lippia sidoides (Verbenaceae) essential oils, and their major compounds under N. corniger and C. brevis, respectively. The essential oils and its compounds were toxic to N. corniger and C. brevis. These treatments reduced the behaviour and walking of termites, as well showed repellent effect. From these results, we have strongly evidences that A. trilobata and L. sidoides, as well as their constituints could be used in control strategies, on a substitute and/or complimentary way, of N. corniger and C. brevis.